Big magic : creative living beyond fear - Gilbert, Elizabeth (New York Riverhead Books, 2015)
"From the worldwide bestselling author of Eat Pray Love: the path to the vibrant, fulfilling life you've dreamed of. Readers of all ages and walks of life have drawn inspiration and empowerment from Elizabeth Gilbert's books for years. Now this beloved author digs deep into her own generative process to share her wisdom and unique perspective about creativity. With profound empathy and radiant generosity, she offers potent insights into the mysterious nature of inspiration. She asks us to embrace our curiosity and let go of needless suffering. She shows us how to tackle what we most love, and how to face down what we most fear. She discusses the attitudes, approaches, and habits we need in order to live our most creative lives. Balancing between soulful spirituality and cheerful pragmatism, Gilbert encourages us to uncover the "strange jewels" that are hidden within each of us. Whether we are looking to write a book, make art, find new ways to address challenges in our work, embark on a dream long deferred, or simply infuse our everyday lives with more mindfulness and passion, Big Magic cracks open a world of wonder and joy"--
Courage -- Enchantment -- Permission -- Persistence -- Trust -- Divinity.
105895
Keywords: Creative ability; Inspiration; Magical thinking; Confidence; Courage; Conduct of life; Self-Help -- Motivational & Inspirational; Body, Mind & Spirit -- Inspiration & Personal Growth; Self-Help -- Personal Growth -- General